ANALISIS KEMANDIRIAN FISKAL DAN POTENSI EKONOMI DALAM PEMEKARAN WILAYAH: STUDI KASUS CALON DOB PROVINSI KEPULAUAN BUTON - Adzam, Muh (PRIMA EKONOMIKA, 2025)
Southeast Sulawesi Province, which has a large area with geographical characteristics divided between mainland and islands, faces challenges in terms of accessibility and equitable development. One of the proposed solutions to overcome this problem is the expansion of the island region. This study adopts several analysis methods, including the Degree of Fiscal Autonomy, Location Quotient (LQ), Shift-Share, and the Williamson Index, to evaluate the level of fiscal independence, leading sectors that have the potential to support the economy of the expansion region, and factors inhibiting fiscal development in the candidate New Autonomous Region (DOB) of the Buton Islands Province. In terms of financial capacity, the candidate DOB region of the Buton Islands Province is still categorized as "lacking". However, this does not necessarily become an obstacle to the expansion process, considering that fiscal decentralization aims to encourage regional independence and reduce dependence on the central government. Strategies that can be implemented to strengthen fiscal independence in this region include optimizing potential sectors, such as fisheries and mining. In addition, targeted government policies are needed to increase the effectiveness of resource management and ensure equitable distribution of economic infrastructure development in the island region.